DEVELOPMENT OF THE SUSTAINABLE INNOVATION ECOSYSTEM AREA IN INDONESIA AND IT’S OBSTACLES - Jangkung Raharjo; Iwan Iwut Tritoasmoro; Bandiyah Sri Aprillia (Politeknik Negeri Bengkalis, 2021)
Recently, several regions in Indonesia have been active in developing sustainable innovation ecosystem areas. This is inseparable from the birth of several policies that encourage it. However, there are still many obstacles to be found. Commitment from stakeholders, determination of focus areas to be developed, management human resources who focus on area management, availability of early adopters greatly affect the sustainability of the area. Several lessons learned and breakthroughs in area management in ensuring sustainability are discussed in this paper. From several keywords for success, stakeholder commitment is the main key to the success of the sustainable innovation ecosystem area.